Thermal Induced Conductance of KOH Etched Silicon Surface - Lamichhane, Shobha Kanta (Kathmandu University Journal of Science, Engineering and Technology, 2010)
Anisotropic KOH etch rate of silicon is found to vary with thermal agitation along with crystal plane orientation. In this work, experimental results of etch rate is found with their unusual values of activation energy along different planes. The various sites that an atom can occupy are not equivalent of their energy; some are more favorable to removal than others. In this paper attention is given to demonstrate thermal activation influences the behavior of etching mechanism as well as surface morphology. Low-voltage contact mode atomic force microscopy (AFM) has been employed to analyze the morphology of the etched silicon surface at relevant temperature. With temperature evolution the width of the forbidden energy gap is going down and hence conductivity is rises. Keywords: Anisotropy; Etch rate; MEMS; SOI; AFM; Contact mode. DOI: 10.3126/kuset.v6i1.3314 Kathmandu University Journal of Science, Engineering and Technology Vol.6(1) 2010, pp79-88